2018
DOI: 10.1186/s41077-018-0071-8
|View full text |Cite
|
Sign up to set email alerts
|

Status of Nordic research on simulation-based learning in healthcare: an integrative review

Abstract: BackgroundBased on common geography, sociopolitics, epidemiology, and healthcare services, the Nordic countries could benefit from increased collaboration and uniformity in the development of simulation-based learning (SBL). To date, only a limited overview exists on the Nordic research literature on SBL and its progress in healthcare education. Therefore, the aim of this study is to fill that gap and suggest directions for future research.MethodsAn integrative review design was used. A search was conducted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…As simulation has become increasingly prevalent in nursing education, there has been a growing need for research on the effects of simulation (Mancini et al, 2019). A large number of studies have been conducted in the last 10-15 years, utilizing a range of qualitative and quantitative approaches (Hayden et al, 2014;Laschinger et al, 2008;Lapkin et al, 2010;Husebø et al, 2018;Yuan et al, 2012). However, the results of many of these studies have been unclear, often having small sample sizes, lacking control groups, and with some results pointing to positive effects of simulation while others fail to find any.…”
Section: Referencementioning
confidence: 99%
“…As simulation has become increasingly prevalent in nursing education, there has been a growing need for research on the effects of simulation (Mancini et al, 2019). A large number of studies have been conducted in the last 10-15 years, utilizing a range of qualitative and quantitative approaches (Hayden et al, 2014;Laschinger et al, 2008;Lapkin et al, 2010;Husebø et al, 2018;Yuan et al, 2012). However, the results of many of these studies have been unclear, often having small sample sizes, lacking control groups, and with some results pointing to positive effects of simulation while others fail to find any.…”
Section: Referencementioning
confidence: 99%
“…12 An integrative review on SBL in the Nordic countries showed that the number of published studies has increased since the early 1990s. 13 Recent studies highlight the use of high-fidelity simulation (HFS) for different professionals, often with different emergency scenarios. High-fidelity simulation enables multiple learning objectives to be achieved in a realistic and secure context for nursing staff.…”
Section: Introductionmentioning
confidence: 99%
“…5 Simulação é definida como um processo dinâmico envolvendo a criação de uma oportunidade hipotética que incorpora uma representação autêntica da realidade, facilita o envolvimento ativo (do participante) e integra as complexidades da aprendizagem prática e teórica com oportunidade de repetição, feedback, avaliação e reflexão. 6 A articulação da teoria e prática tem sido apontada como mecanismo eficaz no ensino superior, pois estimula o aluno na construção de um profissional promovido pela maturidade para atuar em diversas situações, além de oferecer oportunidades de aprendizagem e treinamento através da discussão reflexiva sobre a situação ocorrida ao estimular o pensando crítico e reflexivo do estudante. 7 A educação clínica baseada em simulação é uma técnica de aprendizagem experiencial, que envolve colocar os alunos em situações de atendimento ao paciente criadas por instrutores, a fim de maximizar a aprendizagem em situações reais que os alunos podem encontrar.…”
Section: Introductionunclassified